2020
DOI: 10.3389/fphar.2020.00404
|View full text |Cite|
|
Sign up to set email alerts
|

The Use of Peripheral Blood-Derived Stem Cells for Cartilage Repair and Regeneration In Vivo: A Review

Abstract: Background: Peripheral blood (PB) is a potential source of chondrogenic progenitor cells that can be used for cartilage repair and regeneration. However, the cell types, isolation and implantation methods, seeding dosage, ultimate therapeutic effect, and in vivo safety remain unclear. Methods: PubMed, Embase, and the Web of Science databases were systematically searched for relevant reports published from January 1990 to December 2019. Original articles that used PB as a source of stem cells to repair cartilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 88 publications
(311 reference statements)
0
19
0
Order By: Relevance
“…The use of PBSCs for cartilage repair and regeneration has been demonstrated to be safe in animal and human studies[ 17 ]. In this study, PBSCs were applied for the first time to treat OCD, thus avoiding more tedious collection and in vitro expansion, such as those of adipose-and bone marrow-derived stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PBSCs for cartilage repair and regeneration has been demonstrated to be safe in animal and human studies[ 17 ]. In this study, PBSCs were applied for the first time to treat OCD, thus avoiding more tedious collection and in vitro expansion, such as those of adipose-and bone marrow-derived stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood became an alternative source of MSCs as they can be harvested easily with minimally invasive procedures and isolated by density gradient centrifugation. PB-MSCs can be used in an autologous and allogenic manner, and also, they can be used as a non-cultured or culture-expanded treatment for cartilage repair and regeneration [ 66 ]. Some researchers argue that the number of PB-MSCs in circulation is low [ 67 ], but their number can be increased in the bloodstream by stimulation using granulocyte colony-stimulating factor (G-CSF).…”
Section: Biological Perspectivementioning
confidence: 99%
“…Another study demonstrated good evidence of articular cartilage repair, an increase in cartilage thickness as well as enhanced physical function by use of repeated injections of PBSC into the damaged joint (93). A recent review article established the use of PBMSCs in cartilage repair and regeneration to be very safe and efficacious (94). In phase II clinical trial on the use of PBSCs in an arthritic knee, it was found that these cells increase the mean cartilage thickness and improve the quality of life (95).…”
Section: Peripheral Blood Derived Mscs (Pb-mscs)mentioning
confidence: 99%